Project Time Scheduling Analysis Using the Critical Path Method and Program Evaluation and Review Techniques on the Sapphire Shophouse Project – Cimanggis Golf Estate - Al Faqih Azzhami Kusworo; Rifaldi Adi Saputra (Jurnal Teknik dan Science, 2026)
The construction project of Ruko Sapphire – Cimanggis Golf Estate experienced several delays, resulting in discrepancies between the planned schedule outlined in the S-Curve and the actual conditions in the field. These delays were caused by technical issues with the reinforcement fabrication machine, inconsistencies between structural and architectural stair drawings, rescheduling of concrete casting due to weather and the availability of a concrete pump truck. This study aims to analyze the project scheduling using two methods: the Critical Path Method (CPM), to identify the critical path and determine the minimum project duration, and the Program Evaluation and Review Technique (PERT), to estimate optimistic, most likely, and pessimistic time durations as well as the probability of completing the project on schedule. The research was conducted using a descriptive quantitative approach with primary data (observations and interviews) and secondary data (S-Curve). The results show that both CPM and PERT provide consistent, realistic, and accurate duration estimates, helping contractors identify critical activities, reduce the risk of delays, and provide a more reliable basis for project time planning.